2013
DOI: 10.1371/journal.pone.0082048
|View full text |Cite
|
Sign up to set email alerts
|

Geotemporal Analysis of Neisseria meningitidis Clones in the United States: 2000–2005

Abstract: BackgroundThe detection of meningococcal outbreaks relies on serogrouping and epidemiologic definitions. Advances in molecular epidemiology have improved the ability to distinguish unique Neisseria meningitidis strains, enabling the classification of isolates into clones. Around 98% of meningococcal cases in the United States are believed to be sporadic.MethodsMeningococcal isolates from 9 Active Bacterial Core surveillance sites throughout the United States from 2000 through 2005 were classified according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…However, there is also some evidence for differences in the incidence of particular variants at particular times. For example, a study of IMD isolates in the United States from 2000 to 2005 ( 30 ) indicated that the most common clone belonged to serogroup Y and shared the same fine type as the Swedish strain type YI, although it is difficult to assess if this clone is identical to YI in the absence of WGS data. We have shown that the expansion of serogroup Y disease in Sweden was mostly due to the increase of subtype 1 of the previously described strain type YI ( 9 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also some evidence for differences in the incidence of particular variants at particular times. For example, a study of IMD isolates in the United States from 2000 to 2005 ( 30 ) indicated that the most common clone belonged to serogroup Y and shared the same fine type as the Swedish strain type YI, although it is difficult to assess if this clone is identical to YI in the absence of WGS data. We have shown that the expansion of serogroup Y disease in Sweden was mostly due to the increase of subtype 1 of the previously described strain type YI ( 9 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a US study, 10% of meningococcal disease cases (2000–2005) could be assigned to a geo-temporal cluster (about a third of clusters – serogroup B). Molecular characterization of isolates, combined with geo-temporal analysis, was found useful in detecting the spread of virulent meningococcal clones and transmission patterns [11]. A study from Germany using a combination of molecular fine typing and spatio-temporal analysis revealed that the proportion of IMD cases in spatio-temporal clusters was 4·2% [12].…”
mentioning
confidence: 99%
“…[53]. In Oregon in the mid-1990s, the USA with the same antigenic profile as the Norwegian strains (B:15:P1.7,16) caused the majority of IMD in parts of Washington State and the outbreak had a similar profile to that in Norway -predominantly affecting teenagers and with a high case fatality rate (10%), though with the highest mortality in older adults (aged 55-88) [54,55]. Most recently, in 2013, two college outbreaks occurred in the USA, which prompted the first deployment of the investigational 4CMenB vaccine, the first vaccine capable of eliciting antibody against serogroup B strains used for outbreak control in the USA.…”
Section: Clonal Complex 32 Outbreaksmentioning
confidence: 99%